Improving the quality of care for patients at increased risk for type 2 diabetes at Onandjokwe Intermediate Hospital, Oshikoto Region, Namibia - Kenga, Louis Dikolela (Stellenbosch : Stellenbosch University, 2018)
Thesis (MFamMed)--Stellenbosch University, 2018.